The Effect Of Corporate Advertising And Social Campaigns On Consumer Perceptions: A Case Study Of Coca-Cola's 'Together Tastes Better' Campaign In Indonesia During The Covid-19 Pandemic - Muhammad Rozan Fikri; Vivi Silvia Huri; Lilis Satriah; Imron Rosyidi; Mohammad Afid Syafiri (Jurnal Dakwah dan Komunikasi, 2026)
Purpose − This study aims to analyze the influence of corporate advertising, especially in the form of social campaigns, on consumer perception of the Coca-Cola brand during the COVID-19 pandemic in Indonesia. The main issue examined was how the "Together Tastes Better" campaign can create an emotional connection with consumers while conveying relevant social messages about togetherness in the face of adversity.   Method − A qualitative approach is used with the case study method, which allows researchers to explore in depth how audiences respond to advertising in the context of local social and cultural settings. The data collection technique involved semi-structured interviews, participatory observation, and documentation, with participants consisting of consumers exposed to the campaign through social media and digital platforms.   Findings − Key findings from the study show that these ads successfully elicit emotional engagement from audiences, enhance the relationship between Coca-Cola and social values such as togetherness, and strengthen the brand image in the eyes of consumers. These findings contribute to the understanding of corporate advertising that prioritizes social and cultural issues, as well as the influence of social media in amplifying message impact. In conclusion, corporate advertising that incorporates social values can strengthen relationships with consumers and increase brand loyalty. The study suggests that companies should make better use of social media as an effective advertising distribution channel, and recommends further research to explore the impact of advertising in the broader context of local culture.